Role of the runt‐related transcription factor (RUNX) family in prostate cancer. (22nd March 2021) - Ashe, Hannah; Krakowiak, Patryk; Hasterok, Sylwia; Sleppy, Rosalie; Roller, Devin G.; Gioeli, Daniel
Abstract : Prostate cancer (PCa) is a very complex disease that is a major cause of death in men worldwide. Currently, PCa dependence on the androgen receptor (AR) has resulted in use of AR antagonists and antiandrogen therapies that reduce endogenous steroid hormone production. However, within two to three years of receiving first‐line androgen deprivation therapy, the majority of patients diagnosed with PCa progress to castration‐resistant prostate cancer (CRPC). There is an urgent need for therapies that are more durable than antagonism of the AR axis. Studies of runt‐related transcription factors (RUNX) and their heterodimerization partner, core‐binding factor subunit b (CBFβ), are revealing that the RUNX family are drivers of CRPC. In this review, we describe what is presently understood about RUNX members in PCa, including what regulates and is regulated by RUNX proteins, and the role of RUNX proteins in the tumor microenvironment and AR signaling. We discuss the implications for therapeutically targeting RUNX, the potential for RUNX as PCa biomarkers, and the current pressing questions in the field. Abstract : Studies of runt‐related transcription factors (RUNX) and their heterodimerization partner, core‐binding factor subunit Β, are revealing that the RUNX family are drivers of castration‐resistant prostate cancer. RUNX family member expression changes during prostate cancer progression. RUNX proteins interact with a multitude of proteins and have pleiotropic effects. RUNX proteins are potential biomarkers and attractive therapeutic targets for the treatment of prostate cancer.